Kompilasi syarahan sembelit: kenali penyelesaiannya - Jamaludin, Sumaiyah @ ThandarSoe; Sowtali, Siti Noorkhairina; Abdul Wahab, Patimah; Hassan, Masmunaa (2020)
This compilation of seminar notes is a part of the Intellectual Property (IP) required to be produced under the allocation of KTP-RIGS18-0004 grant. The power point slide is prepared based on the previous Ph.D study entitled "Chronic constipation among the elderly in Kelantan, Malaysia: expreience, prevalance and the impacts on quality of life". It is a compilation of 4 main topics delivered during the workshop conducted on the 4th November 2019. This workshop is known as Program Pemindahan Ilmu (KTP), kerjasama antara Kulliyyah Kejururawatan Universiti Islam Antarabangsa Malaysia dan Kementerian Kesihatan Malaysia, Sembelit: kenali penyelesaiannya. the workshop was taken place in Kulliyyah of Nursing Auditorium between 8.00am to 5.00pm.